2017
DOI: 10.1136/annrheumdis-2017-211682
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of subcutaneous tocilizumab in systemic sclerosis: results from the open-label period of a phase II randomised controlled trial (faSScinate)

Abstract: ObjectivesAssess the efficacy and safety of tocilizumab in patients with systemic sclerosis (SSc) in a phase II study.MethodsPatients with SSc were treated for 48 weeks in an open-label extension phase of the faSScinate study with weekly 162 mg subcutaneous tocilizumab. Exploratory end points included modified Rodnan Skin Score (mRSS) and per cent predicted forced vital capacity (%pFVC) through week 96.ResultsOverall, 24/44 (55%) placebo-tocilizumab and 27/43 (63%) continuous-tocilizumab patients completed wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
128
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(144 citation statements)
references
References 38 publications
(32 reference statements)
3
128
0
7
Order By: Relevance
“…The use of rituximab as a rescue therapy is also increasing, with some observational data supporting its effectiveness in this context . Tocilizumab was only occasionally suggested, and this could be due to results of a phase III trial not yet being available along with a lack of experience and access currently in routine practice . The fourth line of treatment may include referral for ongoing clinical trials and HSCT for selected patients .…”
Section: Discussionmentioning
confidence: 99%
“…The use of rituximab as a rescue therapy is also increasing, with some observational data supporting its effectiveness in this context . Tocilizumab was only occasionally suggested, and this could be due to results of a phase III trial not yet being available along with a lack of experience and access currently in routine practice . The fourth line of treatment may include referral for ongoing clinical trials and HSCT for selected patients .…”
Section: Discussionmentioning
confidence: 99%
“…This drug was also implicated in other inflammatory conditions that involve a fibrotic phenotype, such as SS [17]. Results from the phase II randomized controlled trial (faSScinate) of SS patients showed forced vital capacity (FVC) stabilization within the TCZ receiving SS patients in comparison to placebo controls [22], as well as in placebo-treated patients who later transitioned to TCZ in the open label period [23].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the immune cell activation and fibrosis were significantly suppressed in IL‐6R knockout mice. In fact, tocilizumab, an anti‐IL‐6R antibody that inhibits the binding of IL‐6 and IL‐6R, suppressed the development of SSc‐ILD in addition to skin sclerosis amelioration . Collectively, IL‐6 is thought to be important for the progression of fibrosis in SSc‐ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of IL‐6 to IL‐6R forms a complex with signal‐transducing receptor subunit gp130, resulting in the activation of various immune cells . Through these functions, IL‐6 plays crucial roles in the pathogenesis of several autoimmune diseases including SSc . IL‐6 expression is increased in the serum and skin of patients with SSc, and high serum IL‐6 levels are associated with the severity of skin sclerosis and ILD as well as reduced survival .…”
Section: Introductionmentioning
confidence: 99%